Non-Invasive Physical Plasma Generated by a Medical Argon Plasma Device Induces the Expression of Regenerative Factors in Human Gingival Keratinocytes, Fibroblasts, and Tissue Biopsies - Benedikt Eggers; Matthias Bernhard Stope; Jana Marciniak; Werner Götz; Alexander Mustea; James Deschner; Marjan Nokhbehsaim; Franz-Josef Kramer (Biomedicines, 2022)
After oral surgery, intraoral wound healing and tissue regeneration is an important factor for the success of the entire therapy. In recent years, non-invasive medical plasma (NIPP) has been shown to accelerate wound healing, which would be particularly beneficial for patients with wound healing disorders. Since the application of NIPP in dentistry has not been sufficiently understood, the aim of the present study was to investigate the effect of a medical argon plasma device on gingival cells. Human gingival fibroblasts, keratinocytes, and tissue biopsies were treated with NIPP for different durations. Crucial markers associated with wound healing were examined at the mRNA and protein levels by real-time PCR, ELISA and immunohistochemistry. NIPP treatment led to an increase in Ki67 and MMP1 at mRNA and protein levels. NIPP application lasting longer than 60 s resulted in an increase in apoptotic genes at mRNA level and superficial damage to the epithelium in the tissue biopsies. Overall, our experimental setup demonstrated that NIPP application times of 30 s were most suitable for the treatment of gingival cells and tissue biopsies. Our study provides evidence for potential use of NIPP in dentistry, which would be a promising treatment option for oral surgery.